DIFFERENCES IN SPINE DEFORMITIES, VISCERAL FAT AND MOTOR ABILITIES BETWEEN ACTIVE AND INACTIVE STUDENTS (Fiep Bulletin - online, 2014)
The aim of this study was to evaluate differences in the prevalence of spinal deformities, body mass index (BMI ), waist circumference (WC), explosive power and flexibility between students who are systematically involved in physically activities and inactive students. This study included 74 male students aged 19-23, divided into two groups. Group A consisted of 34 students that are involved in programmed physical activity at least 3 times a week, while Group B consisted of 40 inactive students. Assessment of spine status is done by physician, BMI was the body mass (kg)/height (m)2 ratio, while the WC was a waist circumference measure. Motor abilities tests were: standing medicine ball throw (4kg), standing long jump and sit and reach test. Statistical analysis is done by SPSS program. Active students had less spine deformities than inactive students (p
Keywords: deformities; explosive power; BMI